The study of the biological characteristics and pests of strawberry varieties in the conditionsof ANAU’s greenhouse - Gabrielyan, G. S.; Mkrtchyan, A. L.; Gasparyan, N. A.; Amiryan, Q. R.; Asatryan, S. S. (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
In a hydroponic greenhouse such fruit and vegetable crops are cultivated that have the ability to produce a double crop during the vegetation period. Strawberry (Fragaria ananassa Duch.) is such crop and we chose it for our research. Strawberry varieties grown in hydroponic greenhouses ensure a long-lasting, continuous, high quality and quantity harvest thanks to the created and controlled microclimate, regulated norms and timings of irrigation and nutrition. The period of fruit blossoming, ripening, and the formation of inflorescences occurs quickly. Monitoring is carried out, the dynamics of the development of pests and diseases is controlled, and the pest and disease control measures are implemented at the right times. According to product evaluation indicators the varieties Albion and San Andreas outperformed Malga and Murano varieties. Ուսումնասիրության համար մեր կողմից ընտրվել է ելակը (Fragaria ananassa Duch.), որը հենց այդպիսի մշակաբույս է: Հիդրոպոնիկ ջերմատանը մշակվող ելակի սորտերն ապահովում են բարձր որակի և քանակի բերք՝ շնորհիվ արհեստականորեն ստեղծվող և վերահսկվող միկրոկլիմայի, ոռոգման և սնուցման կարգավորվող նորմերի և ժամկետների, պտղի ծաղկման, հասունացման, ծաղկակիրների առաջացման կարճ ժամանակահատվածի և այլն: Կատարվում է մոնիթորինգ, վերահսկվում է վնասատուների և հիվանդությունների զարգացման դինամիկան, և ճիշտ ժամկետներում իրականացվում են պայքարի միջոցառումներ: Ըստ ապրանքային գնահատման ցուցանիշների` Ալբիոն և Սան Անդրեաս սորտերը գերազանցել են Մալգա և Մուռանո սորտերին: Для нашего исследования была выбрана земляника (Fragaria ananassa Duch.), которая является именно такой культурой. Сорта земляники, выращенные в гидропонных теплицах, обеспечивают высокое качество и количество урожая за счет искусственно созданного и регулируемого микроклимата, регулируемой нормы и сроков, цветения, созревания плодов, короткого периода формирования цветоносов и др. Проводится мониторинг, контролируется динамика развития вредителей и болезней, своевременно реализуются меры борьбы. Сорта Альбион и Сан-Андреас превзошли сорта Мальга и Мурано по показателям оценки продукции
Keywords: Botany